Pengaruh Sektor Pariwisata Terhadap Pendapatan Asli Daerah (PAD) Di Kabupaten Bogor Dari Tahun 2014-2021 Dengan Metode Regresi Linier Berganda - Agus Tri Indah K; Harun Al Rasyid (Owner : Riset dan Jurnal Akuntansi, 2023)
Local governments now have the freedom to organize and manage their own government affairs and the interests of the local community in accordance with statutory regulations since the regional autonomy system came into force on January 1, 2001 as stipulated in Law Number 22 of 1999, which has been amended by Law no. 32 of 2004. The purpose of this study was to examine the impact of tourism on local revenue in Bogor Regency, tourist visits on local revenue and the impact of tourist-oriented accommodation facilities on local revenue in Bogor Regency. The time of this research was conducted in May 2021. This study used a quantitative descriptive research methodology, associative research, which is research that aims to find out the relationship between two or more variables. Types and sources of secondary data in the 2014–2021 research period. The results showed that the number of tourist visitors and regional income in Bogor Regency did not have a positive relationship as shown by Tcount(0.827) > Ttable(2.571), so it had no positive effect on Locally-generated revenue. For accommodation and local income in Bogor Regency there is no positive relationship as indicated by accommodation with the results Tcount(0.998) < Ttable(2.571), so it has no positive effect on Locally-generated revenue. while the latest research, with 2 tourist and accommodation variables, has no significant effect on local revenue, because for simultaneous calculations, t table =(2;8-2)=(2;6)=5.14, test results simultaneous Fcount(0.435) > Ttable(5.14) , then the conclusion of tourists and accommodation simultaneously has no effect onLocally-generated revenue